Factors Associated With Low Physical Activity in Two Latin American Populations at Risk of Developing Type 2 Diabetes: An Exploratory Analysis - Acosta, Tania; Tuesca, Rafael; Florez, Karen; Barengo, Noël C.; Anillo, Luis; Flórez-García, Victor; Acosta, Jorge; Carvajal, Liliana; de la Rosa, Sandra; Pachón, María Julieta; Aschner, Pablo (Frontiers in Public Health, 2021)
Low level of physical activity is a risk factor for chronic non-communicable diseases. Specifically, people at risk of Type 2 Diabetes (T2D) have shown to benefit from being physically active. The objective of this study was to explore what factors were associated with low physical activity in people at high risk of T2D living in Bogota and Barranquilla, Colombia. Methodology: Cross-sectional study using baseline data from a quasi-experimental clinical trial (PREDICOL Project). The study included 1,135 participants of Bogota and Barranquilla that presented a high risk of developing T2D according to the Finnish Diabetes Risk Score (>12 points) and who underwent an oral glucose tolerance test. The main outcome variable was the level of physical activity assessed by the International Physical Activity Questionnaire. Unadjusted and adjusted logistic regression analysis were used to calculate odds ratios (OR) and the corresponding 95% confidence intervals (CI). Results: In total, 72.5% of the study participants had low level of physical activity. Participants in the age group between 45 and 54 years showed 74% greater odds of having low physical activity compared with the youngest age group (OR 1.74, 95% CI 1.1 −2.8). People living in Barranquilla were eight times more likely to have low physical activity compared with those in Bogotá D.C. (OR 8.1, 95% CI 5.7 to 11.4). Conclusion: A large proportion of the population at risk of developing D2T in two large cities of Colombia have a sedentary lifestyle. Interventions should be designed and implemented in order to increase physical activity in these populations.